The effect of rootstocks on morphological, physiological, and gene expression characters of citrus seedlings grown under drought condition - Nirmala Friyanti Devy; Siti Subandiyah; Sri Widyaningsih; Hardiyanto Hardiyanto; Farida Yulianti; Dita Agisimanto; Agus Sugiyatno; Mutia Dwiastuti (Horticultural Science)
To date, 'Japansche Citroen' (JC) has only been used commercially as a rootstock in Indonesia; however, the use of suitable rootstock remains challenging because of water limits in different places. The morphological, physiological, and gene expression changes of one-and-a-half-year-old mandarin cv. 'Keprok Batu 55'  (KB) and sweet orange cv. 'Manis Pacitan'  (MP) budded onto 'Japansche citroen' (JC), 'Rough Lemon' (RL), 'Salam' (S), 'Volkameriana' (V), and 'Cleopatra Mandarin' (C) rootstocks, subjected to six-week drought-stress conditions, were examined under a shade house. The experiment was conducted in Junrejo Subdistrict ( ± 990 m a.s.l.), Batu City, East Java Province, Indonesia, from January 2022 to May 2023. The experimental design was a factorial randomized block design with two factors: rootstocks as factor I and two citrus species as factor II, with three replications. A low shoot/root (S/R) ratio indicates much more root development than shoots observed in KB/C (0.89) and MP/RL (0.87) plants under drought conditions; the MP/RL plant had the greatest stomatal density (16.0/0.015 mm2) and percentage of stomatal closure (58.8%). In this condition, it had lower leaf relative water content (RWC) than the control, with comparatively high RWC ranging from 45-55% in KB/JC, KB/S, MP/C, and MP/RL. The drought did not affect cell membrane damage, although this did slightly increase the quantity of chlorophyll a, b, and carotenoids (P < 0.05). Aside from that, leaf proline and total soluble sugar levels were higher in the dryness than in the control, with the combination of KB/C (331.6 μ mol proline/g fresh weight), MP/JC, and MP/RL plants having the highest (347.9 and 337.1 μmol proline/g fresh weight). Meanwhile, the plants with the greatest quantities of soluble sugar were KB/C (35.9 mg/g dry weight) and MP/V (75.3 mg/g dry weight). Regardless of scion-rootstock interaction, KB enhanced the relative quantity of several genes such as 1-Aminocyclopropane-1-carboxylate (ACC) synthase, Chlase, ethylene receptors (ETR1), osmotin, plasma membrane instrinsic proteins (PIP1), and PIP2 allowing it to respond more effectively to drought stress conditions. In contrast, MP only increased Chlase and ETR1 ones. Under drought conditions, the KB/C and MP/RL combinations are assumed to be more adaptable than others.